Analysis of the protective effect of setting isolation piles outside the foundation pit on the underpass tunnel side. (July 2022) - Wei, Gang; Qi, Yongjie; Chen, Chunlai; Zhang, Shuming; Qian, Chengli; Zhou, Jian
Abstract: Excavating and unloading a foundation pit cause deformation or even destruction of any existing adjacent tunnel. In construction projects, isolation piles are often set between the foundation pit and tunnel to protect the existing tunnel. The aim of the present study was to investigate the horizontal displacement law of an existing tunnel outside the isolation piles as a result of foundation pit excavation, so as to analyze the protective effect of isolation piles on the existing tunnel. The unloading effect of the sidewalls, the unloading effect of the base of the foundation pit, and the deflection deformation of the isolation piles were considered. A three-dimensional mechanical calculation model for foundation pits, isolation piles, and existing tunnels was established. Based on the Mindlin's solution, the calculation formula of the additional stress caused by the unloading of the foundation pit was deduced. Based on the energy variation method, the calculation formula for the deflection deformation of the isolation piles was derived. Using the mirror image method, the calculation formula for the horizontal displacement of the existing tunnel caused by the deformation of the isolation pile was derived. The influence of different spacing distances between isolation piles on the horizontal displacement of an existing tunnel was studied. The research results showed that the calculation results in this study were consistent with the actual engineering data available and numerical simulation results. It was concluded that the installation of isolation piles could effectively reduce the horizontal displacement of tunnels and fulfil a beneficial protective role, and that the protective effect gradually increases as the distance between isolation piles is reduced.